Macrophage-derived extracellular vesicles from Ascaris lumbricoides antigen exposure enhance Mycobacterium tuberculosis growth control, reduce IL-1β, and contain miR-342-5p, miR-516b-5p, and miR-570-3p that regulate PI3K/AKT and MAPK signaling pathways - Pushpamithran, Giggil; Blomgran, Robert (Frontiers in Immunology, 2024)
Background: Helminth coinfection with tuberculosis (TB) can alter the phenotype and function of macrophages, which are the major host cells responsible for controlling Mycobacterium tuberculosis (Mtb). However, it is not known whether helminth infection stimulates the release of host-derived extracellular vesicles (EVs) to induce or maintain their regulatory network that suppresses TB immunity. We previously showed that pre-exposure of human monocyte-derived macrophages (hMDMs) with Ascaris lumbricoides protein antigens (ASC) results in reduced Mtb-infection driven proinflammation and gained bacterial control.This effect was entirely dependent on the presence of soluble components in the conditioned medium from helminth-antigen pre-exposed macrophages.Methods: Our objective was to investigate the role of EVs released from helminth antigenexposed hMDMs, on Mtb-induced proinflammation and its effect on Mtb growth in hMDMs. Conditioned medium from 48h pre-exposure with ASC or Schistosoma mansoni antigen (SM) was used to isolate EVs by ultracentrifugation. EVs were characterized by immunoblotting, flow cytometry, nanoparticle tracking assay, transmission electron microscopy, and a total of 377 microRNA (miRNA) from EVs screened by TaqMan array. Luciferase-expressing Mtb H37Rv was used to evaluate the impact of isolated EVs on Mtb-growth control in hMDMs.Results: EV characterization confirmed double-membraned EVs, with a mean size of 140nm, expressing the classical exosome markers CD63, CD81, CD9, and flotillin-1. Specifically, EVs from ASC conditioned medium increased the bacterial control in treatment-naïve hMDMs and attenuated Mtb-induced IL-1 at five days post-infection. Four miRNAs showed unique upregulation in response to ASC exposure in five donors. Pathway enrichment analysis showed MAPK and PI3K-AKT signaling pathways regulated. Among the mRNA targets, relevant for regulating inflammatory responses and cellular stress pathways, CREB1 and MAPK13 were identified. In contrast, SM exposure showed significant regulation of the TGF- signaling pathway with SMAD4 as a common target.Overall, our findings suggest that miRNAs in EVs released from helminthexposed macrophages regulate important signaling pathways that influence macrophage control of Mtb and reduce inflammation. Understanding these interactions between helminth-induced EVs, miRNAs, and macrophage responses may inform novel therapeutic strategies for TB management.